ILLICIT ENRICHMENT DALAM PENEGAKKAN HUKUM PENGAMBILAN IKAN SECARA TIDAK SAH (ILLEGAL FISHING) DI WILAYAH PERAIRAN INDONESIA - Raharjo, Endiyono; Saputra, Rio (Faculty of Law, University of Muhammadiyah Malang, 2017)
With a sea area of more than 5.8 million kmÂ² Indonesia into the fields were wet for the perpetrators of illegal fishing, but it is not only those involved in illegal fishing are committing exploitation of marine resources in it, due to ease and expedite actions of those involved in illegal fishing have interference from government officials and private entrepreneurs who help in exploiting marine resources in it. Illicit enrichment officials and private entrepreneurs in committing permudahan and facilitate the exploitation of marine resources by those involved in illegal fishing would be a bad precedent for officials and the private sector, which should keep and explore marine resources so that their needs and income that should belong to the state. Government that is supported by law enforcement in the rigor and candor regulations should be able to make the deterrent effect of government officials and private entrepreneurs who do illicit enrichment.